PENGARUH KUALITAS PELAYANAN, STORE ATMOSPHERE DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA (STUDI KASUS PADA KONSUMEN DEALER TUNGGUL SAKTI SEJAHTERA SEMARANG) - Desi Trihatmi Yaumil Asri; Wahyu Hidayat; Ngatno Ngatno (Universitas Diponegoro, 2015)
Over time human needs are increasingly complex, to support human needs so it takes such transportation, an own vehicles. one of the vehicle is Honda motorcycle. Honda motorcycle purchasing in Semarang done by Astra Motor Region of Semarang is supported by some official dealer in Semarang. One of the official dealers is Tunggul Sakti. In the latest five years 2010-2014 Honda motorcycle purchasing in Tunggul Sakti Sejahtera dealer cannot reach the target, only in 2013 and 2014 it can reach the target. There are some factors influencing the purchasing decision in the dealer. They are service quality, store atmosphere, and location. The aim of this research is to figure out if the service quality, store atmosphere, and location influence the purchasing decision of Honda motorcycle in Tunggul Sakti dealer Semarang. The numbers of taken samples are 98, those are taken with purposive sampling technique. The collecting data techniques are questionnaire and interview. The analysis methods used are cross tabulation, correlation experiment, determination, simple linier regression, multiple linier regression, T experiment and F experiment. The result of the research reveals that partially or simultaneously that there is an influence in the service quality, store atmosphere and location towards purchasing decision. The given suggestion for Tunggul Sakti Sejahtera dealer is that they had better improve the service quality of the Tunggul Sakti Sejahtera dealer’s employees by minimizing mistake, adding an AC so that the room will be cooler, and doing any exhibition in central crowd to get closer with consumers.